Interleukin-1 beta gene deregulation associated with chromosomal rearrangement: a candidate initiating event for murine radiation-myeloid leukemogenesis? - Silver, A; Boultwood, J; Breckon, G; Masson, W; Adam, J; Shaw, A; Cox, R (1989)
The incidence of acute myeloid leukemia (AML) in CBA/H mice following exposure to single acute doses of ionizing radiation has previously been determined. A high proportion of these AMLs are characterized by rearrangement of murine chromosome 2 in the C2 and/or E5-F regions, and there is evidence that these events are a direct consequence of radiation damage to multipotential hemopoietic cells. Using a combination of in situ chromosome hybridization and mRNA analyses, we show that the cytokine gene interleukin-1 beta (IL-1 beta) is encoded in the chromosome 2 F region and is translocated in a chromosome 2---2 rearrangement in an x-ray-induced AML (N36). Also, IL-1 beta is specifically deregulated in N36 and in two other chromosome 2-rearranged AMLs but not in a fourth, which has two cytogenetically normal chromosome 2 copies. We suggest that radiation-induced specific chromosome 2 rearrangement associated with IL-1 beta deregulation may initiate murine leukemogenesis through the uncoupling of normal proliferative control mechanisms in multipotential hemopoietic cells.